Dependency and Hardship in the Gig Economy: The Mental Health Consequences of Platform Work. (March 2022) - Glavin, Paul; Schieman, Scott
The authors investigate the relationship between platform work engagement and worker mental health on the basis of two nationally representative samples of Canadian workers. Integrating insights from the job demands–resources model and Schor's idea of "platform dependence, " the authors examine whether a dependent attachment to the platform economy is associated with poorer mental health. Multivariate analyses reveal that dependent platform workers report higher levels of psychological distress than secondary platform workers, wage workers, and the traditional self-employed. In contrast to work conditions, which contribute little to these distress patterns, financial strain explains approximately 50 percent of dependent platform workers' higher distress. Contingency analyses reveal that financial strain also exacerbates the mental health penalties associated with dependent platform work. These findings support a "dependent-precarity" perspective of platform work stress, raising questions about the future health challenges posed by platform work in a postpandemic economy.